Religious Harmony in Urban Communities Post Toa Regulation: A Case Study in Yogyakarta City - Ahmad Thoriq Akhsan Ramdhani; Budiman Yunus; Azhari Maulana; Andhika Gilang Prayoga (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This journal will present various perspectives from the general public, mosque officials, and community leaders in Yogyakarta, responding to the loudspeaker regulations issued by the Ministry of Religion through Circular Letter Number 05 of 2022, which outlines the Guidelines for the Use of Loudspeakers in Mosques and Mushalas. This research was conducted using descriptive qualitative analysis through observations and interviews. The study's findings will be elaborated in detail, discussing arguments presented by respondents from both the Muslim community and other religious groups. By thoroughly and clearly examining the diverse responses to this issue and including fundamental arguments, this research aims to serve as a reference for future scholars. The differing opinions presented here serve as a valuable knowledge base, contributing to the methods and strategies for resolving the ongoing debate. This empirical data in the form of opinions can be utilized as a reference in guiding policy actions and other empowerment initiatives, including awareness and outreach programs.